2014
DOI: 10.1016/j.jcbs.2014.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Idiographic Assessment Template-Questionnaire (FIAT-Q): Initial psychometric properties

Abstract: The evidence based assessment (EBA) movement stresses the importance of psychological measures with strong psychometric properties and clinical utility. The Functional Idiographic Assessment Template system (FIAT; Callaghan, 2006) is a functional analytic behavioral approach to the assessment of interpersonal functioning for use with therapies like Functional Analytic Psychotherapy (FAP; Kohlenberg & Tsai, 1991). While research has begun to demonstrate the clinical utility of the FIAT, its psychometric propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 47 publications
(58 reference statements)
0
9
0
2
Order By: Relevance
“…To measure interpersonal relationships, items were adapted from Darrow, Callaghan, Bonow and Follette (2014). Sample items include "People don't like the way I ask for things," "I have problems being close to others".…”
Section: Interpersonal Relationshipmentioning
confidence: 99%
“…To measure interpersonal relationships, items were adapted from Darrow, Callaghan, Bonow and Follette (2014). Sample items include "People don't like the way I ask for things," "I have problems being close to others".…”
Section: Interpersonal Relationshipmentioning
confidence: 99%
“…Landes, Kanter, Weeks, and Busch (2013) used both the FIAT-Q and FIAT-DA as clinical and research tools to examine idiographic behavior in clients and found promising results. In terms of psychometrics, Darrow, Callaghan, Bonow, and Follette (2014) examined convergent and discriminative validity with survey measures and construct validity in factor analyses and found supportive preliminary data. Beyond these studies, FIAT-Q research is limited, specifically for the use of such tools on therapist/trainee behavior.…”
Section: Clinical Toolsmentioning
confidence: 80%
“…Each domain score is examined independently, with high scores indicating greater dysfunction. The FIAT-Q has demonstrated good psychometrics properties (Darrow et al, 2014; Leonard, Knott, Lee, et al, 2014). The FIAT-Q was used as a clinical tool in this study.…”
Section: Methodsmentioning
confidence: 99%
“…These problems are classified in 5 classes: assertion of needs (class A), which refers to the way clients express their needs, desires, and values to others, and includes scape and avoidance responses; bidirectional communication (class B), which is related to clients' skills to effectively give feedback to others' behaviors, or to accept it; conflict (class C), which denotes clients' difficulties to respond adequately to interpersonal conflictive situations; interpersonal closeness (class D), that represents clients' behaviors that obstruct the building of close relationships and reduce the opportunities to get in touch with social reinforcements; and emotional experience and expression (class E), which is associated with clients' difficulties to effectively express feelings and to identify and respond accordingly to others' emotional responses (Callaghan, 2006). The FIAT-Q has shown adequate internal consistency in previous studies (.94) (Darrow, Callaghan, Bonow, & Follette, 2014).…”
Section: Functional Idiographic Assessment Template (Fiat-q)mentioning
confidence: 95%